Reported patterns of vaping to support long-term abstinence from smoking: a cross-sectional survey of a convenience sample of vapers - Gentry, Sarah Victoria (Harm Reduct J, 2020)
BACKGROUND: E-cigarettes are the most popular aid to smoking cessation attempts in England and the USA. This research examined associations between e-cigarette device characteristics and patterns of use, tobacco-smoking relapse, and smoking abstinence. METHODS: A convenience sample of 371 participants with experience of vaping, and tobacco-smoking abstinence and/or relapse completed an online cross-sectional survey about e-cigarettes. Factors associated with smoking relapse were examined using multiple linear and logistic regression models. RESULTS: Most participants were self-reported long-term abstinent smokers (86.3%) intending to continue vaping. Most initiated e-cigarette use with a vape pen (45.8%) or cig-a-like (38.7%) before moving onto a tank device (89%). Due to missing data, managed through pairwise deletion, only around 70 participants were included in some of the main analyses. Those using a tank or vape pen appeared less likely to relapse than those using a cig-a-like (tank vs. cig-a-like OR = 0.06, 95% CI 0.01–0.64, p = 0.019). There was an inverse association between starting self-reported e-cigarette liquid nicotine concentration and relapse, interacting with device type (OR = 0.79, 95% CI 0.63–0.99, p = 0.047), suggesting that risk of relapse may have been greater if starting with a low e-cigarette liquid nicotine concentration and/or cig-a-like device. Participants reported moving from tobacco-flavored cig-a-likes to fruit/sweet/food flavors with tank devices. CONCLUSIONS: Knowledge of how people have successfully maintained tobacco-smoking abstinence using vaping could help other tobacco smokers wishing to quit tobacco smoking through vaping.